Programa computacional en Python para resolver Flujos de potencia del Sistema Eléctrico de Potencia. - Jaramillo Ordoñez, Gilson Eduardo (2025)
Power flow analysis is fundamental for planning and designing future power system expansions and determining the optimal operating conditions of existing systems. This iterative process requires a low error tolerance, making it essential to develop tools that ensure efficiency and accuracy in applying the methods. In this context, the primary objective of this research is to develop a Python algorithm for solving power flows. The first part consists of developing the algorithm based on the Gauss-Seidel method. Subsequently, voltage regulation elements have been incorporated to develop a more complete analysis. Specifically, the transformer tap, capacitor banks, and synchronous motors have been modeled. In terms of data storage, we have chosen to use a plain text file. Two types of data are stored in this file: the first corresponds to the initial values of the lines and busbars, and the second corresponds to the results obtained from the power flow solution. In addition, the text file allows easy access to the initial data, to modify these values and to obtain variations in the results. To validate the performance of the developed algorithm, model problems were solved, and the results were compared with the PowerWorld program. The calculated error is small, generally less than, which has allowed validation of the accuracy and efficiency of the algorithm.